A growing need for youth mental health services in Canada: examining trends in youth mental health from 2011 to 2018. (2020) - Wiens, K.; Bhattarai, A.; Pedram, P.; Dores, A.; Williams, J.; Bulloch, A.; Patten, S.
Abstract: Aims: The mental health of youth is continually changing and requires reliable monitoring to ensure that adequate social and economic resources are allocated. This study assessed trends in mental health among Canadian youth, 12–24 years old. Specifically, we examined the prevalence of poor/fair perceived mental health, diagnosis of mood and anxiety disorders, suicidality, perceived stress and sleep problems, substance use, and mental health consultations. Methods: Data were collected from eight cycles of the annual Canadian Community Health Survey (2011–2018). Prevalence of mental health outcomes was calculated from each survey, and meta-regression was used to assess trends over time. In the absence of a significant trend over time, the eight cycles were pooled together using meta-analysis techniques to gain precision. Trends in prevalence were assessed for the overall sample of youth (12–24 years) and separately for male and female adolescents (12–18 years) and young adults (19–24 years). Results: The prevalence of poor/fair perceived mental health, diagnosed mood and anxiety disorders, and past-year mental health consultations increased from 2011 to 2018, most strongly among young adult females. Past-year suicidality increased among young adult females but did not change for other age and sex groups. Notably, the prevalence of binge drinking decreased by 2.4% per year for young adult males, 1.0% for young adult females and 0.7% per year for adolescent males, while staying relatively stable for adolescent females. Prevalence of cannabis use declined among adolescents before legalisation (2011–2017); however, this trend did not persist in 2018. Instead, the 2018 prevalence was 5.6% higher than the 2017 prevalence (16.3 v . 10.7%). The combined prevalence of other illicit drug use was stable at 4.6%; however, cocaine use and hallucinogens increased by approximately 0.2% per year. Conclusions: Our findings highlight a growing need for youth mental health services, as indicated by a rise in the prevalence of diagnosed mood and anxiety disorders and past-year mental health consultations. The reason for these observed increases is less apparent – it may represent a true rise in the prevalence of mental illness, or be an artefact of change in diagnostic practices, mental health literacy or diminishing stigma. Nonetheless, the findings indicate a need for the health care system to respond to the rising demand for mental health services among youth.